2022
DOI: 10.3390/ma15031225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selected Properties of Sodium Alginate-Based Hydrogel Material—Mechanical Strength, μDIC Analysis and Degradation

Abstract: The search for ideal solutions for the treatment of urethral stenosis continues. This includes developing the material, design, while maintaining its optimal and desired properties. This paper presents the results of the research conducted on sodium alginate-based hydrogel material (AHM), which may be used as a material for stents dedicated to the treatment of pathologies occurring in the genitourinary system. In order to determine the selected parameters of the AHM samples, strength and degradation tests, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
(70 reference statements)
1
11
0
1
Order By: Relevance
“…The most suitable technique for forming a tubular hydrogel is to immerse the polymer matrix in alginate and crosslink using divalent cations ( Figure 4 c). This is confirmed by previous studies describing the crosslinking of sodium alginate with calcium cations, as well as an extensive analysis of the literature describing the effect and relationship between alginate concentration and crosslinking agent [ 86 , 99 , 102 , 103 ].…”
Section: Methodssupporting
confidence: 84%
“…The most suitable technique for forming a tubular hydrogel is to immerse the polymer matrix in alginate and crosslink using divalent cations ( Figure 4 c). This is confirmed by previous studies describing the crosslinking of sodium alginate with calcium cations, as well as an extensive analysis of the literature describing the effect and relationship between alginate concentration and crosslinking agent [ 86 , 99 , 102 , 103 ].…”
Section: Methodssupporting
confidence: 84%
“…The studies showed that hydrogel crosslinked with calcium ions showed a lower mechanical strength compared to the one crosslinked with Ba 2+ cations (Figure 32). The researchers attributed the difference to the increased barium affinity to alginate monomers (G blocks), resulting in a hydrogel by forming the egg-box structure, characteristic of alginate NPs [108].…”
Section: Stiffness Of the Materialsmentioning
confidence: 99%
“…Formulation of NBCs in the nanoscale can increase the viscosity. Ahmad et al reported that the viscosity of starchbased NPs dispersion was influenced by the shape, size, and distribution of the starch Strain-strain analysis plot for the proposed sodium alginate-based material cross-linked with Ca 2+ or Ba 2+ cations using different cross-linking times after 72 h cross-linking time [108].…”
Section: Flow Curves (Steady Shear Flow)mentioning
confidence: 99%
See 1 more Smart Citation
“…matrix have broadly used as implanted stents, tissues, and occluders. [ 25 ] At present, ureter stricture has become common trouble for males, [ 26 ] which could be concerned by the scarring, causing from that the scar tissue replaces the spongy tissue. [ 27 ] The commonly used treatment method for these ureter canal narrowing is implanted stents, which commonly use metal as the material matrix.…”
Section: Introductionmentioning
confidence: 99%